Representation of Diagnosis and Nursing Interventions in OpenEHR Archetypes - Gomes, Denilsen Carvalho; Abreu, Nuno; Sousa, Paulino; Moro, Claudia; Carvalho, Deborah Ribeiro; Cubas, Marcia Regina (Applied Clinical Informatics, 2021)
Objective The study aimed to represent the content of nursing diagnosis and interventions in the openEHR standard.Methods This is a developmental study with the models developed according to ISO 18104: 2014. The Ocean Archetype Editor tool from the openEHR Foundation was used.Results Two archetypes were created; one to represent the nursing diagnosis concept and the other the nursing intervention concept. Existing archetypes available in the Clinical Knowledge Manager were reused in modeling.Conclusion The representation of nursing diagnosis and interventions based on the openEHR standard contributes to representing nursing care phenomena and needs in health information systems.
Keywords: nursing informatics; health information interoperability; standardized nursing terminology; nursing notes; patient records